Liberalism and libraries. The project of creating a public library in Valencia during the Liberal Triennium - C. Muñoz Feliu, Miguel (Revista General de Información y Documentación, 2016)
It is studied the project of creating a public library in the city of Valencia from the librariesof the convents and monasteries suppressed during the Liberal Triennium. It is analyzed thedisentailment legislation and its application in library matters and the purpose and nature of this newpublic library promoted by the Sociedad Económica de Amigos del País de Valencia, which wouldhave been directed by the scholar Jaime Villanueva. The lack of resources of all kinds and thecentralist vision of the Government of Madrid, for whom overrode the interests of the BibliotecaNacional de Cortes, suspended the project. The return to absolutism postponed it until 1835.
Keywords: Library policy; Ecclesiastical disentailment; Liberal Triennium; Sociedad Económica de Amigos del País de Valencia; Jaime Villanueva y Astengo; Valencia.